Due Diligence of Transport Infrastructure Operators Sustainability: A Circular Economy Driven Approach - Dimitriou, Dimitrios; Karagkouni, Aristi (Frontiers in Sustainability, 2022)
Renewable energy usage, waste, and water management are all issues that airports must address in order to be able to adapt to changing situations and address environmental sustainability principles. This paper deals with an analysis of the development principle of airport renewable green facilities and activities by reviewing the areas that impact the sustainable transition of international mobility and freight hubs, such as airports. By a systemic review, the special focus is on airport landside business, in which comprehensive landside facilities data gathering framework, defining the context and key trends in landside development framework in European airports, serving popular tourist destinations in Mediterranean region. The analysis is based on the breakdown of the airports’ key environmental aspects related to renewable green facilities and provides key message to planners and decision makers about the development of renewable green activities in airports located in popular tourist destinations as enabler for shifting them into greener infrastructure. Conventional wisdom is to provide a clear, coherent and well support view for the linkage of airports’ sustainable transition with the development of renewable green facilities and activities in their landside area, providing a great picture for planners and decision makers in terms of managing airports serving tourist destinations.